Gastrointestinal Stromal Tumors of the Pancreas - Saif, Muhammad Wasif; Hotchkiss, Susan; Kaley, Kristin (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Original building of Yale School of Medicine, formerly a hotel built by James Hillhouse at the corner of Grove and Prospect Streets.